Identification of Expression Patterns and Potential Prognostic Significance of m5C-Related Regulators in Head and Neck Squamous Cell Carcinoma - Han, Zhenyuan; Yang, Biao; Wang, Yu; Zeng, Xiuxia; Tian, Zhen (Frontiers in Oncology, 2021)
5-Methylcytosine (m5C) methylation is a major epigenetic technique of RNA modification and is dynamically mediated by m5C “writers,” “erasers,” and “readers.” m5C RNA modification and its regulators are implicated in the onset and development of many tumors, but their roles in head and neck squamous cell carcinoma (HNSCC) have not yet been completely elucidated. In this study, we examined expression patterns of core m5C regulators in the publicly available HNSCC cohort via bioinformatic methods. The differentially expressed m5C regulators could divide the HNSCC cohort into four subgroups with distinct prognostic characteristics. Furthermore, a three-gene expression signature model, comprised of NSUN5, DNMT1, and DNMT3A, was established to identify individuals with a high or low risk of HNSCC. To explore the underlying mechanism in the prognosis of HNSCC, screening of differentially expressed genes, followed by the analysis of functional and pathway enrichment, from individuals with high- or low-risk HNSCC was performed. The results revealed a critical role for m5C RNA modification in two aspects of HNSCC: (1) dynamic m5C modification contributes to the regulation of HNSCC progression and (2) expression patterns of NSUN5, DNMT1, and DNMT3A help to predict the prognosis of HNSCC.